Non-canonical activity of retinoic acid in relation to the activation of protein kinases in transformed cells of different origin - A. D. Enikeev; A. V. Komelkov; I. B. Zborovskaya; S. A. Galetsky; G. O. Skryabin; E. M. Tchevkina (Успехи молекулярной онкологии)
Background. The non-canonical activity of retinoic acid (RA) was discovered relatively recently and consists in the rapid activation of intracellular signaling pathways by the mechanisms not related to the transcriptional activity of the RA nuclear receptors. Separate data suggest that this activity can stimulate the processes of malignancy and contribute to the formation of tumor cell resistance to RA as a therapeutic agent. However, little is known about the mechanisms of this activity. It is also unclear how universal this effect is; does the RA-dependent activation of different signaling protein kinases occur in the same cells, and whether activation of these kinases is interrelated.Materials and methods: cultivation of non-small cell lung cancer cells and neuroblastoma cells under standard conditions and with incubation with all-trans retinoic acid (ATRA); immunoblotting.Results. Here we studied the effect of ATRA on the activation of Akt and Erk1/2 protein kinases depending on the incubation time. The analysis revealed RA-dependent activation of both kinases in all studied non-small cell lung cancer and neuroblastoma cell lines. Activation of Akt and Erk1/2 occurred at five minutes of incubation, which corresponds to the non-transcriptional (non-canonical) activity of the RA, however, further activation kinetics of the two kinases differed essentially.Conclusion. We found that ATRA causes rapid activation of Erk1/2 and Akt protein kinases in both non-small cell lung cancer and neuroblastoma cells. The differences in the kinetics of RA-dependent stimulation of these two kinases suggest that their activation is mediated by independent mechanisms.